Primary Payer Status Is Associated With the Use of Nerve Block Placement for Ambulatory Orthopedic Surgery. Issue 3 (1st May 2012) - Tighe, Patrick J.; Brennan, Meghan; Moser, Michael; Boezaart, Andre P.; Bihorac, Azra
Abstract : Introduction: Although more than 30 million patients in the United States undergo ambulatory surgery each year, it remains unclear what percentage of these patients receive a perioperative nerve block. We reviewed data from the 2006 National Survey of Ambulatory Surgery to determine the demographic, socioeconomic, geographic, and clinical factors associated with the likelihood of nerve block placement for ambulatory orthopedic surgery. The primary outcome of interest was the association between primary method of payment and likelihood of nerve block placement. In addition, we examined the association between type of surgical procedures, patient demographics, and hospital characteristics with the likelihood of receiving a nerve block. Methods: This cross-sectional study reviewed 6000 orthopedic anesthetics from the 2006 National Survey of Ambulatory Surgery data set, which accounted for more than 3.9 million orthopedic anesthetics when weighted. The primary outcome of this study addressed the likelihood of receiving a nerve block for orthopedic ambulatory surgery according to the patient's primary method of payment. Secondary end points included differences in demographics, surgical procedures, adverse effects, complications, recovery profile, anesthesia staffing model, and total perioperative charges in those with and without nerve block. Results: Overall, 14.9% of anesthetics in this sample involved a peripheral nerve block. Length of time in postoperative recovery, total perioperative time, and total charges were less for those receiving nerve blocks. Patients were more likely to receive a nerve block if their procedures were performed in metropolitan service areas (odds ratio [OR], 1.86; 95% confidence interval [CI], 1.19–2.91; P = 0.007) or in freestanding surgical facilities (OR, 2.27; 95% CI, 1.74–2.96; P < 0.0001) and if payment for their surgery was supported by government programs (OR, 2.5; 95% CI, 1.01–6.21; P = 0.048) or private insurance (OR, 2.62; 95% CI, 1.12–6.13; P = 0.03) versus self-pay or charity care. Conclusions: For patients receiving ambulatory orthopedic surgery in the United States, our results suggest that geographic and socioeconomic factors are associated with different likelihoods of perioperative peripheral nerve block placement.